Perbedaan Titik Fokus Rias Wajah Antara Makeup Editorial Dan Rias Pengantin Tradisional Daerah - Eny Widhia Agustin; Salma Oktavina; Nazla Aulia Rosa; Nur Atikah; Rahmanda Dwi Pangestika; Putri Wahyu Zunaedah; Rima Affiani Adhiningrum (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
Facial makeup is a form of aesthetic art that plays an important role in enhancing a person’s appearance. In its development, makeup has various styles and functions depending on the purpose of its use. Two types of makeup that have distinct characteristics are editorial makeup and traditional bridal makeup. The different purposes of these two makeup styles lead to differences in determining the focal points of facial makeup. This study aims to analyze the differences in facial makeup focal points between editorial makeup and traditional regional bridal makeup. The research used a qualitative approach with a library research method. The data were obtained from various scientific literature sources such as journal articles, books, and other relevant academic publications related to facial makeup techniques and characteristics. The collected data were analyzed using descriptive qualitative analysis to describe and compare the characteristics of the two types of makeup. The results of the study indicate that editorial makeup tends to have more flexible and expressive focal points because it aims to support visual concepts in photography, fashion magazines, and other visual media. The focal point can be placed on the eyes, lips, or facial structure using dramatic and creative techniques. In contrast, traditional regional bridal makeup emphasizes facial balance and harmony while adhering to cultural values and traditional standards. The focal points in bridal makeup are generally on the eyes, eyebrows, and lips to create an elegant and captivating appearance while maintaining the bride’s natural facial character. In addition, the success of editorial makeup is measured by its visual impact and photogenic quality in front of the camera, whereas the success of traditional bridal makeup is assessed based on beauty, harmony with traditional attire, and the durability of the makeup throughout the wedding ceremony. Therefore, the differences in the purpose of makeup application significantly influence the techniques, focal points, and success standards of each makeup style